Some Geometric Properties of Lacunary Sequence Spaces Related to Fixed Point Property - Chirasak Mongkolkeha; Poom Kumam (Abstract and Applied Analysis)
The main purpose of this paper is considering the lacunary sequence spaces defined by Karakaya (2007), by proving the property (β) and Uniform Opial property.